PENGARUH E-SERVICE QUALITY DAN E-TRUST TERHADAP MINAT BELI PADA E-COMMERCE BLIBLI.COM DI KOTA BEKASI - Alicia Prasasti, Fania; Ratnasari, Ina; Fathan Muhammad, Rabhi (Journal for Management Student (JFMS), 2022)
This study aims to examine and analyze The Effect of E-Service Quality and E-Trust on Buying Interest on E-Commerce Blibli.com in Bekasi City. This research was conducted using quantitative methods with descriptive and verification approaches, namely: collecting, presenting, analyzing and testing hypotheses and making conclusions and suggestions. The sample of this study was collected using the Issac-Michael formula and 5% error rate and non-probability sampling techinique with a purposive sampling approach. The analytical technique used in this study is the technique of scale range analysis and path analysis with the help of the Succesive Internal Method (MSI), the Microsoft Excel 2019 computer program and the SPSS version 20 application. The results showed that e-service quality, e-trust and buying interest in e-commerce Blibli.com in Bekasi City are in the good category. This means that the e-service quality provided by e-commerce Blibli.com is considered capable of providing confidence to consumers to make purchases in e-commerce Blibli.com. Partially e-service quality has a significant effect on buying interest while e-trust does not have a significant effect on buying interest. and e-service quality, e-trust simultaneously affects buying interest.